Novel insights into the isolation of extracellular vesicles by anion exchange chromatography - Koch, Leon F.; Best, Tatjana; Wüstenhagen, Elena; Adrian, Klaus; Rammo, Oliver; Saul, Meike J. (Frontiers in Bioengineering and Biotechnology, 2024)
Extracellular vesicles (EVs) are membrane structures enclosed by a lipid bilayer that are released into the extracellular space by all types of cells. EVs are involved in many physiological processes by transporting biologically active substances. Interest in EVs for diagnostic biomarker research and therapeutic drug delivery applications has increased in recent years. The realization of the full therapeutic potential of EVs is currently hampered by the lack of a suitable technology for the isolation and purification of EVs for downstream pharmaceutical applications. Anion Exchange Chromatography (AEX) is an established method in which specific charges on the AEX matrix can exploit charges on the surface of EVs and their interactions to provide a productive and scalable separation and purification method. The established AEX method using Eshmuno® Q, a strong tentacle anion exchange resin, was used to demonstrate the principal feasibility of AEX-based isolation and gain insight into isolated EV properties. Using several EV analysis techniques to provide a more detailed insight into EV populations during AEX isolation, we demonstrated that although the composition of CD9/63/81 remained constant for tetraspanin positive EVs, the size distribution and purity changed during elution. Higher salt concentrations eluted larger tetraspanin negative vesicles.